PENGARUH MEDIA AUDIO VISUAL PADA PEMBELAJARAN MUSIK ENSAMBEL KELAS VIII DI SMP NEGERI 5 PARIAMAN - M. Riko Nurrohim; Ardipal Ardipal; Marzam Marzam (SENDRATASIK UNP, 2017)
AbstractThis research was initiated by the implementation of music art learning based on syllabus of curriculum 2013, in the ensemble music lesson it was found that teacher still use conventional methods of teaching. The role of teacher is not demonstration samples to student is not correct, teachers also have not untilized the media to proride teaching materials to students. This has an impact on the value of students who are still less good is 60% of students get grades under the KKM and also 40% of students get a fitting value on KKM. The purpose of this research is to describe what  elements and effects of audio visual media on learning to play ensemble music.The type of this research is descriptive by using qualitative approach, the object of this research is a students of 8th grade of SMP N 5 Pariaman. In this case reseaechers suggest to teachers to use audio visual media in conveying the material that will be taught to students is learning to play ensemble music.Bused on this research, the following results are obtained: first, the elements of audio visual media itself, form; a. its easy to move; b. can be replayed or overheard and viewed again and again; c. make students really understand the conten of the subject matter with more indepth analysis and make students think more specific about the subject matter; d. can overcomethe limited experience possessed by learnes; e. can stimulate active participation of hearing students, and can develop imagination such as writing, drawing and etc; f. audio visual media allows for  interaction between learness and the surrounding environment; and g. increase the attractiveness and attention of students. The second results, there was a change of attitude toward students in learning, what is shown through student behavior becomes more serious, passionate about learning, and the student score rose to 60% of the students were in the KKM and 40% of the students were above the KKM.Key Words: Media, Audio visual, Learning